Safety Behaviours Assessment in Academic Institution: A Case Study in Unit Laboratory - Mohd Sam, Mohd Fathullah (Universiti Teknologi PETRONAS, 2013)
The purpose of this research is to discover the unsafe acts or behaviours of the students that might lead to accidents or injuries in UTP laboratories. Hence, a safety behaviours assessment should be conducted to assess the unsafe acts or any behaviour in unsafe condition. Mostly, the technique used is based on observation system whereby safety observation will be piloted in during the students conduct their experiments which is including equipment and chemical handling and safety behaviours in the laboratories. Safety interventions will be applied in order to assist the students and as guidance to reduce or prevent any accidents or injuries. It is estimated that after a certain period of time, the statistic of unsafe behaviours will decrease even after without safety interventions. At the end of the research, this safety training model using behaviours-based safety training program should be applicable for young adults especially during their tertiary education. In addition, the school or college should also be able to develop and integrate this safety program as part of compulsory method as it will be helpful before the students are exposed to the real-life working situations. This is because most of the accident and injury case in work-place are due to improper safety training and lack of experiences by the newbies or the fresh graduated students. Therefore, this research will help them to gain some knowledge and experiences before getting to work after graduated from college or school.